1983
DOI: 10.1099/0022-1317-64-11-2493
|View full text |Cite
|
Sign up to set email alerts
|

Serological Studies on Tomato Golden Mosaic Virus, a Geminivirus

Abstract: SUMMARYParticles of tomato golden mosaic virus (TGMV), purified by an improved procedure, were used to prepare an antiserum which in gel double-diffusion tests with homologous virus gave a single precipitin line and had a titre of 1/256. TGMV was shown to be serologically related to another geminivirus, cassava latent virus, and distantly related to a leafhopper-transmitted geminivirus, beet curly top virus. No relationship could be detected to four other leaf hopper-transmitted geminiviruses.Golden mosaic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
27
1
Order By: Relevance
“…The relationship between ACMV and EuMV has also been detected by geldiffusion precipitin tests (R. W. Fulton, personal communication). The apparent relationships previously reported of BCTV with ACMV (Sequeira & Harrison, 1982) and TomGMV (Stein et al, 1983) were not confirmed and were possibly caused by anti-host antibodies in the serum. No relationship was detected in the test reported here between BCTV and any of the whiteflytransmitted viruses.…”
Section: Dna Sequence Homologiescontrasting
confidence: 67%
See 1 more Smart Citation
“…The relationship between ACMV and EuMV has also been detected by geldiffusion precipitin tests (R. W. Fulton, personal communication). The apparent relationships previously reported of BCTV with ACMV (Sequeira & Harrison, 1982) and TomGMV (Stein et al, 1983) were not confirmed and were possibly caused by anti-host antibodies in the serum. No relationship was detected in the test reported here between BCTV and any of the whiteflytransmitted viruses.…”
Section: Dna Sequence Homologiescontrasting
confidence: 67%
“…However, Sequeira & Harrison (1982) detected a serological relationship between ACMV and bean golden mosaic virus (BGMV), and Cohen et al (1983) found that ACMV is serologically related to squash leaf curl virus (SLCV). Similarly, tomato golden mosaic virus (TomGMV) was found to be serologically related to ACMV and BGMV (Stein et al, 1983) and, in addition, weak relationships were reported between beet curly top virus (BCTV) and both ACMV and TomGMV (Sequeira & Harrison, 1982;Stein etal., 1983). Of these viruses, ACMV, BGMV, SLCV and TomGMV are transmitted by the whitefly Bemisia tabaci, whereas the others have leafhopper vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one days post-inoculation, DNA was extracted from all plants as described previously (Stein, Coutts, and Buck, 1983). The presence or absence of replicated A and B DNA was detected by DNA gel blot analysis using 32P-labeled A-specific or 6-specific riboprobes prepared from TGMV subclones in pGEM plasmids (Promega, Madison, WI).…”
Section: Analysis Of Tgmv Replication In Lnfected Plantsmentioning
confidence: 99%
“…TGMV capsid polypeptide was subjected to SDS-PAGE in three lanes of a 15 ~ polyacrylamide gel alongside marker proteins and then immobilized on nitrocellulose by Western blotting (Towbin et al, 1979). The nitrocellulose sheet from the blot was cut into three portions: one portion was stained with amido black, the second was probed with an antiserum prepared to TGMV virions (Stein et al, 1983) and the third was probed with the AR1 fusion protein antiserum. Detection of bound antibodies with a Protein A-peroxidase conjugate by probing with the antisera, followed by incubation with 4-chloro-l-naphthol and hydrogen peroxide, were carried out as described by Sherwood (1987).…”
Section: Short Communicationmentioning
confidence: 99%
“…None of the protein products of these ORFs has been directly identified. We now present evidence which proves that ORF AR1 codes for the coat protein.TGMV was isolated from systemically infected Nicotiana benthamiana plants and purified by sucrose density gradient centrifugation as described by Stein et al (1983). To ensure that the preparation was completely free from host proteins, virus was further purified by centrifugation for 20 h at 115 000 g in a caesium sulphate density gradient in a Beckman SW50.1 rotor.…”
mentioning
confidence: 99%